2018
DOI: 10.1155/2018/5879281
|View full text |Cite
|
Sign up to set email alerts
|

A Typical Immune T/B Subset Profile Characterizes Bicuspid Aortic Valve: In an Old Status?

Abstract: Bicuspid valve disease is associated with the development of thoracic aortic aneurysm. The molecular mechanisms underlying this association still need to be clarified. Here, we evaluated the circulating levels of T and B lymphocyte subsets associated with the development of vascular diseases in patients with bicuspid aortic valve or tricuspid aortic valve with and without thoracic aortic aneurysm. We unveiled that the circulating levels of the MAIT, CD4+IL−17A+, and NKT T cell subsets were significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…The lowest levels seen in the T‐cell subsets examined were that of mucosal‐associated invariant T cells and natural killer T cells . For the B‐cell subsets the lowest levels were seen in CD19+ cells, naïve B IgD+ CD27− cells, IgD+ CD27+ cells (memory switched and unswitched) and double negative B cells . This B and T lymphocyte profile reflects what has been observed in older people, so the study suggests BAV patients seem to have an “old immune system” with an increased inflammatory component, which is more vulnerable to internal and external stressors, frailty, disability, and disease .…”
Section: Immunogenomic Processes and How They Are Overlapped With Immsupporting
confidence: 50%
See 2 more Smart Citations
“…The lowest levels seen in the T‐cell subsets examined were that of mucosal‐associated invariant T cells and natural killer T cells . For the B‐cell subsets the lowest levels were seen in CD19+ cells, naïve B IgD+ CD27− cells, IgD+ CD27+ cells (memory switched and unswitched) and double negative B cells . This B and T lymphocyte profile reflects what has been observed in older people, so the study suggests BAV patients seem to have an “old immune system” with an increased inflammatory component, which is more vulnerable to internal and external stressors, frailty, disability, and disease .…”
Section: Immunogenomic Processes and How They Are Overlapped With Immsupporting
confidence: 50%
“…They also observed a slightly elevated level of the same subsets in patients with thoracic aortic aneurysm (TAA), a trend seen in both BAV and TAV patients; the only exception to elevated levels in TAA patients was for double negative B cell levels . The lowest levels seen in the T‐cell subsets examined were that of mucosal‐associated invariant T cells and natural killer T cells . For the B‐cell subsets the lowest levels were seen in CD19+ cells, naïve B IgD+ CD27− cells, IgD+ CD27+ cells (memory switched and unswitched) and double negative B cells .…”
Section: Immunogenomic Processes and How They Are Overlapped With Immmentioning
confidence: 93%
See 1 more Smart Citation
“…We recently evidenced the presence of distinctive molecular and cellular mechanisms in BAV patients, when compared to tricuspid aortic valve (TAV) patients with or without AAA 1113 . Specifically, we demonstrated an increased allele frequency of some polymorphisms in genes encoding molecules of NO, MMP, ACE pathways 13 , a quantitative reduction in the circulating levels of T and B lymphocytes cell subsets 14 , a deregulation of Notch 1 pathway and circulating endothelial progenitor cell (EPC) 15 number in BAV cases compared to TAV cases, irrespective from the presence of AAA disease.…”
Section: Introductionmentioning
confidence: 91%
“…Possibly changes in both basal immunological status and in the response to surgery exist. One recent paper found that BAV patients have decreased T and B lymphocyte levels and the authors suggested that BAV patients have ‘an old immune system’ which is ‘more easily vulnerable to internal and external stressors’ ( 31 ).…”
Section: Discussionmentioning
confidence: 99%